(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: To describe the knowledge and attitudes of family members of postpartum women toward postpartum depression and examine the association between knowledge and attitudes. Method: A cross-sectional descriptive study was conducted from February to April 2026 among 420 family members of postpartum women at Hai Phong Obstetrics and Gynecology Hospital. Participants were recruited using convenience sampling. Results: Overall, 53.3% of participants had adequate knowledge and 59.5% showed a positive attitude toward postpartum depression. Crisis situations, lack of family support, and domestic violence were the most commonly recognized causes (90.5%). Feeling sad/miserable and sleeping problems were the most frequently identified symptoms (92.9%). Positive attitudes were mainly reflected through empathy toward affected women (94.3%) and willingness to provide support (89.8%). However, 41.4% of participants still believed postpartum depression could be caused by supernatural factors, and only 25.5% agreed that postpartum depression is common among women. Conclusion: More than half of the participants had adequate knowledge and most showed positive attitudes toward postpartum depression. Nevertheless, misconceptions and stigmatizing beliefs were still observed, highlighting the need for community-based educational interventions.